Maturação fisiológica e avaliação do potencial fisiológico de sementes de Campomanesia xanthocarpa O. Berg - Herzog, Neusa Francisca Michelon (2007)
In the present work, were used fruits of Campomanesia xanthocarpa O. BERG, collected in the rural area of Marechal Cândido Rondon - PR, in the months of September 2005 and 2006. The first stage of collecting the fruits were harvested ripe, 8 matrices, brought to the laboratory of Technology Seeds and Mudas. Initially were selected, seeds extracted with the of running water, dried in the shade and then stored in paper bags at room temperature which remained stored for 1 year. In order to acquire a better quality seeds, setting the best time of collection, in the following year, a new collection was held in the same place, as already described above. The fruits were separated into three stages of ripening. The color of the fruit MorkBlogs was compared by Munsel Color Chart For Plant Tissues, described as dark green, yellow-orange and orange intense. The dimensions were evaluated, computed the number of seeds, given the mass, water content of the weight of the fruit and seeds. Moreover, there was the morphology of germination. Tested Performance seeds on substrates of sand and role in the three stages of maturation. Suitable the methodology of the test tetrazólio for the analysis of the physiological seed in the same result, this only at the stage of ripeness intense orange, evaluating external aspects of seed such as: color, shape, and position of hilo micrópila and for the presence or internal absence of the endosperm, position of cotyledons, characteristics of the shaft-cotyledons-intact. The germination of the seed was considered since the issuance of intact until the issue of protófilos, and the seedling considered established when the protófilos were fully expanded. The appropriateness of the methodology of the test tetrazólio were tested the following pre-conditions: withdrawal of the seed husk by scour in cloth, perforation of the husk with needle and incision of seed through cuts. Based on the results found, it was concluded that there was no significant difference in weight of the fruit whole, in diameter and the length of the fruit. The fruits of C. Xanthocarpa showed variations in decreasing moisture content of the fresh weight, from the first stage of development. With respect to morphology of germination, it was observed that the seed is covered by algae, the husk is the type tests and that the embryo mistake it is coiled pigtail and consists of the shaft intact - cotyledons. It was found that the seed on paper at 25 ° C indifferent the presence of photoperiod promoted greater and faster germination. The biggest potential physiological was reached in seed extracted from fruit with yellow-orange pericarp. In tests of tetrazólio, with seed husk submitted by 2:30 hours of imbibition in resolving tetrazólio of 0.5% resulted in better treatment. Three lots with different dates of collection, were evaluated in this test condition and compared to the germination test. Results indicate that the test was effective in the evaluation of the feasibility of seeds of C. Xanthocarpa